ABO Blood Group Incompatibility Protects Against SARS-CoV-2 Transmission - Boukhari, Rachida; Breiman, Adrien; Jazat, Jennifer; Ruvoën-Clouet, Nathalie; Martinez, Salima; Damais-Cepitelli, Anne; Le Niger, Catherine; Devie-Hubert, Isabelle; Penasse, Fanny; Mauriere, Dominique; Sébille, Véronique; Dürrbach, Antoine; et al. (Frontiers in Microbiology, 2022)
ABO blood groups appear to be associated with the risk of SARS-CoV-2 infection, but the underlying mechanisms and their real importance remain unclear. Two hypotheses have been proposed: ABO compatibility-dependence (neutralization by anti-ABO antibodies) and ABO-dependent intrinsic susceptibility (spike protein attachment to histo-blood group glycans). We tested the first hypothesis through an anonymous questionnaire addressed to hospital staff members. We estimated symptomatic secondary attack rates (SAR) for 333 index cases according to spouse ABO blood group compatibility. Incompatibility was associated with a lower SAR (28% vs. 47%; OR 0.43, 95% CI 0.27-0.69), but no ABO dependence was detected in compatible situations. For the second hypothesis, we detected no binding of recombinant SARS-CoV-2 RBD to blood group-containing glycans. Thus, although no intrinsic differences in susceptibility according to ABO blood type were detected, ABO incompatibility strongly decreased the risk of COVID-19 transmission, suggesting that anti-ABO antibodies contribute to virus neutralization.